Bioactivity, chemical and microbial diversity in Alternanthera brasiliana : the influence of endophytes on antibiotic production - Trapp, Marília Almeida (2016)
Alternanthera brasiliana is a plant widely used by Brazilian people as a folk medicine for the treatment of numerous diseases, especially due to its antibiotic properties. Using dereplication strategies, we identified antibiotic compounds as modified fatty acids, which are closely related to oxylipins. The biosynthesis of these compounds could be related with the presence of endophytic bacteria. Thus, we established axenic cultures of A. brasiliana and developed methods for detection and quantification of bacterial cells in plant tissues. We also performed initial re-inoculation experiments with endophytic bacteria isolated from A. brasiliana. In addition, method for quantification of phytohormones and oxylipins in plant tissues were developed. The results reinforced the correlation between both the amount of bacteria and oxylipins in A. brasiliana tissues.